DESIGN OF HEAT EXCHANGER FOR THE PRODUCTION OF SYNTHESIS PbO PARTICLES - Tabita Dwi Vena; Asep Bayu Dani Nandiyanto; Risti Ragadhita; Teguh Kurniawan (Jurnal Ilmiah Flash, 2022)
This study aims to develop and analyze the design of heat exchangers (HE) in the synthesis of PbO particles using a single precursor method. This type of HE shell and tube one-pass is designed to be simple. The specifications of HE equipment are shell length 1.5200 m, shell diameter 0.1361 m, outer tube diameter 0.0334 m, and thickness 0.0243 m. Then the calculation is done manually using the Microsoft Excel application. The results showed that the HE shell and tube design with the one pass type has a laminar flow, with an effective value of 84.66%. Therefore, this heat exchanger with shell and tube one meets the requirements and standards based on effectiveness, but without considering the fouling factor. The results of this analysis can be used as a learning medium in the design process, analysis of heat exchanger performance, and operating mechanisms.